Popular game elements used in designing game-based learning STEM application for school students – A review - Aisyah Nadhirah Juhari; Mimi Hani Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2020)
There are a variety of educational games produced for studies in game-based learning (GBL) with a specific design to achieve the most efficient stage of learning for school students. However, there is a lack of evidence showing the most suitable and effective game element instilled in the GBL STEM application. Most of the papers studied on GBL have proven the effectiveness aspect in other STEM subjects, however very little discussed in the domain of sustainable energy. Thus, this study aimed to analyse the most common game element applied in designing GBL that achieved the best result for students in learning the STEM subjects. Each game element targeted a different kind of learning results such as student’s learning performance, knowledge level, cognitive effect, and enjoyment. A systematic review was conducted following the specification of the PRISMA checklist to examine past studies. After carefully screening the articles, only twelve published articles met the specification. The finding showed that most common game elements included in designing the GBL, dominated by the level of challenges, followed by rewards/items, feedback, clear goal and time pressure. The finding also included the percentage of most STEM subject studied in GBL and the impact from the GBL STEM application. This review hopes to assist researchers in making a better decision when designing a game application for GBL in sustainable energy subject, from the aspect of students’ age and gender.